The Effectiveness of the Implementation of the Norms for the Distribution of Zakat Funds in BAZNAS of Pekalongan City (Articles 25 and 26 of Law No. 23 of 2011) - Jumailah; Ahmad Fauzan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This paper analyzes the effectiveness of implementing norms for the distribution of zakat funds and the implications of their distribution referring to Articles 25 and 26 of Law no. 23 of 2011 concerning Zakat Management and Article 3 PP Number 14 of 2014 concerning its Implementation. This regulation is a guideline for managing zakat funds carried out in Pekalongan City. Research location at BAZNAS Pekalongan City. This type of research is empirical juridical, data is collected from observations and interviews with BAZNAS managers in Pekalongan City. Analysis uses an interactive model. The research results show that the implementation of the distribution of zakat funds at BAZNAS Pekalongan City refers to the norms of Law no. 23 of 2011. However, in fact it is not effective, because to measure the effectiveness and success of law enforcement depends on three elements of the legal system, namely: First, the legal structure, the management of BAZNAS Pekalongan City has been formed. Second, the legal substance is supportive, namely the existence of statutory instruments that regulate Zakat Management. Third, the legal culture of the people of Pekalongan City is predominantly Muslim and they know the obligation to pay zakat, supported by the Mayor's circular about paying zakat at BAZNAS. In this case, efforts to change the position of mustahik into muzaki have not been achieved, but the economic conditions of the mustahik have become capable. Therefore articles 25 and 26 of Law no. 23 of 2011 is not yet effective.